Reinterpreting Classical Islamic Family Law For Sexual Health Education: A Maqāṣid Al-Sharī‘ah-Based Critical Discourse Analysis - Widya Sepalanita; Nina Afiani; Muhammad Maymun; Dahrizal Dahrizal; Lindawati Lindawati (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
This study explores the intersection between classical Islamic family law and sexual health education by analyzing three canonical texts: Fath al-Qarib, Safinat al-Najah, and Uqud al-Lujjayn. While sexual health education has been widely studied within biomedical and rights-based frameworks, its integration with classical Islamic jurisprudence remains limited and fragmented. This study fills a critical gap by systematically analyzing classical fiqh texts as sources of sexual health pedagogy, which has been largely neglected in existing scholarship. Employing a qualitative library-based approach, this research utilizes qualitative content analysis and critical discourse analysis to examine both explicit and implicit dimensions of sexual education within the texts. The analysis is further informed by a maqāṣid al-sharī‘ah perspective and a critical evaluation of gender relations and power structures. The findings show that classical Islamic texts function as normative and pedagogical systems that regulate sexuality through moral discipline, legal boundaries, and implicit ethical instruction. Sexual education is conveyed both explicitly, through marital ethics and conduct, and implicitly, through prohibitions and moral conditioning. However, the study also demonstrates that these texts embed hierarchical gender relations that may limit sexual communication, autonomy, and responsiveness to contemporary sexual health challenges. The study proposes a hybrid ethical-health framework integrating Islamic jurisprudence with contemporary sexual health paradigms. This framework highlights the potential of classical Islamic texts as culturally grounded resources for sexual health education, while emphasizing the need for critical reinterpretation to address issues of gender equity, communication, and reproductive health in modern Muslim societies.